2008
DOI: 10.1038/mp.2008.87
|View full text |Cite
|
Sign up to set email alerts
|

Proton MRS in twin pairs discordant for schizophrenia

Abstract: Proton magnetic resonance spectroscopy ( 1 H MRS) neurometabolite abnormalities have been detected widely in subjects with and at risk for schizophrenia. We hypothesized that such abnormalities would be present both in patients with schizophrenia and in their unaffected twin siblings. We acquired magnetic resonance spectra (TR/TE = 3000/30 ms) at voxels in the mesial prefrontal gray matter, left prefrontal white matter and left hippocampus in 14 twin pairs discordant for schizophrenia (2 monozygotic, 12 dizygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 95 publications
(100 reference statements)
10
111
2
3
Order By: Relevance
“…Our results in elevated choline containing compounds (GPC + PCh) found in the dorsal caudate of FEP patients agrees with previous reports in patients with schizophrenia (Bustillo et al, 2002;Lutkenhoff et al, 2010), and in childhood-onset schizophrenia (O'Neill et al, 2004). Three previous reports have failed to find differences in choline in the cerebellum of patients with schizophrenia (Eluri et al, 1998;Tibbo et al, 2000;Bustillo et al, 2008).…”
Section: Other Metabolitessupporting
confidence: 82%
See 1 more Smart Citation
“…Our results in elevated choline containing compounds (GPC + PCh) found in the dorsal caudate of FEP patients agrees with previous reports in patients with schizophrenia (Bustillo et al, 2002;Lutkenhoff et al, 2010), and in childhood-onset schizophrenia (O'Neill et al, 2004). Three previous reports have failed to find differences in choline in the cerebellum of patients with schizophrenia (Eluri et al, 1998;Tibbo et al, 2000;Bustillo et al, 2008).…”
Section: Other Metabolitessupporting
confidence: 82%
“…Fourth, altered NAAG has been described in schizophrenia. Although NAAG could contribute to the quantification of NAA, it could not be differentiated in a reliable way with the methodology employed in our study (Lutkenhoff et al, 2010). Specific techniques to measure NAAG (Edden et al, 2007) could be used in future studies.…”
Section: Limitationsmentioning
confidence: 99%
“…The glutamate meta-analysis reported increased glutamine and reduced glutamate, in medial frontal single-voxel studies, 6 with progressive reductions with age. These results did not appear related to a more ventral [23][24][25] or dorsal frontal placement. [26][27][28][29][30] However, the quality of the spectral fits is not always clear in these reports (except for [27][28][29] ) and the samples were small (9 to 30 for the schizophrenia groups 6 ).…”
Section: Discussionmentioning
confidence: 52%
“…[26][27][28][29][30] However, the quality of the spectral fits is not always clear in these reports (except for [27][28][29] ) and the samples were small (9 to 30 for the schizophrenia groups 6 ). More recent studies reported increases, [31][32][33][34][35] reductions 25,[36][37][38] and no differences 39 in Glx or glutamate. Two 33,34 of the 5 recent studies documenting elevations involved more ventral regions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, impaired neurotransmission and excitotoxicity after an ischemic insult lead to transient glutamate decrease and glutamine accumulation (Berthet et al, 2011;Lei et al, 2009). In line with this idea, disturbed glutamatergic neurotransmission in schizophrenia leads to altered levels of glutamine, glutamate, and most notably of Gln/Glu, as observed in translational and clinical 1 H MRS studies (Bustillo et al, 2009;Hashimoto et al, 2005;Lutkenhoff et al, 2008;Shirayama et al, 2010;Tayoshi et al, 2009). …”
Section: Discussionmentioning
confidence: 67%